COMPREHENSIVE REVIEW OF NIGELLA SATIVA (SHONIZ): A MULTIFACETED UNANI HERB - Dr. Afeefa Kazmi; Dr. Nauris Quamar; Dr. Md. Razi Ahmad; Dr. Md. Tanwir Alam; Dr. Md. Najibur Rahman; Dr. Sadia Sadaf; Dr. Shamama Usmani; Dr. Mariyam Jameel; Dr. Shabana Noor (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Nigella sativa Linn., commonly known as Shoniz, Kalonji, or Black Cumin, is a cornerstone of Unani medicine, celebrated for its wide-ranging therapeutic applications. Known as “Hab al Barakah” (seed of blessing), it has been traditionally valued for treating numerous ailments. This review synthesizes traditional Unani uses with modern scientific evidence, exploring its phytochemistry, pharmacological properties, and clinical efficacy. Key bioactive compounds, particularly thymoquinone, contribute to its therapeutic effects. Clinical studies demonstrate its effectiveness in managing diabetes, dyslipidemia, asthma, chronic rhinosinusitis, and acne, aligning with its traditional applications. However, limitations such as small sample sizes and lack of standardized protocols highlight the need for further research. This paper underscores N. sativa’s potential as a universal healer, advocating for its integration into evidence-based medicine through rigorous clinical trials.